Needs Analysis of Artificial Intelligence (AI)-Based Digital Comic Media Development in Islamic Religious Education Subjects in Junior High School - Lestari, Sri Umi; Syarifuddin, Syarifuddin; Nurhasan, Nurhasan (Journal of English Language and Education, 2025)
Islamic Religious Education (IRE) plays an important role in shaping the character of students in the digital era, but many challenges are faced, including low interest and motivation of students in learning. This study aims to analyze students' needs for the development of Artificial Intelligence (AI)-based digital comic media as an innovative solution to improve IRE learning in Junior High School. Using a quantitative descriptive method, this study involved 30 students from grade VII of SMP Negeri 7 Sekayu and used a questionnaire to collect data. The results of the analysis showed that 77.3% of students had difficulty understanding material, with only 35% showing interest in the lesson. This fact is balanced by a very high interest (82.8%) in the use of digital comic media. Only 39% of students feel that learning media is currently effective, signaling the need for a more engaging approach. This research brings hope for the development of AI-based digital comic media that is interactive and relevant to students, although limited to one school and a small sample. The suggestion for future research is to involve more schools and explore various other learning mediums to improve student learning outcomes in the field of religious education.